2006
DOI: 10.1091/mbc.e06-03-0243
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Induces Myoblast Differentiation through Cx43 Protein Expression: A Role for a Gap Junction-dependent and -independent Function

Abstract: Although sphingosine 1-phosphate (S1P) has been considered a potent regulator of skeletal muscle biology, acting as a physiological anti-mitogenic and prodifferentiating agent, its downstream effectors are poorly known. In the present study, we provide experimental evidence for a novel mechanism by which S1P regulates skeletal muscle differentiation through the regulation of gap junctional protein connexin (Cx) 43. Indeed, the treatment with S1P greatly enhanced Cx43 expression and gap junctional intercellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 63 publications
3
82
0
Order By: Relevance
“…Cx43 protein is the predominant connexin in skeletal muscle and its involvement in myogenesis and muscle regeneration have been well documented [6,[23][24][25]. We have demonstrated that expression levels of Cx43 are greatly enhanced by S1P in C2C12 skeletal myoblasts and provided the basis for considering the gap junctional protein as an intracellular target of the pro-myogenic action of the sphingolipid [6].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Cx43 protein is the predominant connexin in skeletal muscle and its involvement in myogenesis and muscle regeneration have been well documented [6,[23][24][25]. We have demonstrated that expression levels of Cx43 are greatly enhanced by S1P in C2C12 skeletal myoblasts and provided the basis for considering the gap junctional protein as an intracellular target of the pro-myogenic action of the sphingolipid [6].…”
Section: Introductionmentioning
confidence: 62%
“…We have demonstrated that expression levels of Cx43 are greatly enhanced by S1P in C2C12 skeletal myoblasts and provided the basis for considering the gap junctional protein as an intracellular target of the pro-myogenic action of the sphingolipid [6]. Of interest, Cx43 may also perform a gap junction independent function, acting as an adaptor protein through its interaction with F-actin and associated proteins, and establishing an organization center for intracellular signal transduction [6,26,27]. Like many other membrane proteins, Cx43 also exhibits a rapid turnover (half-life of few hours) controlled by a complex interplay of events involving the protein synthesis/degradation, plasma membrane association, and gap junction internalization.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations